Nicotinamide Adenine Dinucleotide Phosphate Oxidases Are Everywhere in Brain Disease, but Not in Huntington’s Disease? - Villegas, Luisana; Nørremølle, Anne; Freude, Kristine; Vilhardt, Frederik (Frontiers in Aging Neuroscience, 2021)
Huntington’s disease (HD) is an inherited neurodegenerative disorder characterized by neuronal loss and tissue atrophy mainly in striatum and cortex. In the early stages of disease, impairment of neuronal function, synaptic dysfunction and white matter loss precedes neuronal death itself. Relative to other neurodegenerative diseases such as Alzheimer and Parkinson disease and Amyotrophic Lateral Sclerosis, where the effects of either microglia or NADPH oxidases (NOXs) are recognized as important contributors to disease pathogenesis and progression, there is a pronounced lack of information in HD. This despite evidence from human patients that blood monocytes and microglia are activated well before HD clinical symptoms (PET scans), and the clear signs of oxidative stress and inflammation in post mortem HD brain. Habitually, NOX activity and oxidative stress in the central nervous system (CNS) are equated with microglia, but research of the last two decades has carved out important roles for NOX enzyme function in neurons. Here, we will convey recent information about the function of NOX enzymes in neurons, and contemplate on putative roles of neuronal NOX in HD. We will focus on NOX-produced reactive oxygen species (ROS) as redox signaling molecules in/among neurons, and the specific roles of NOXs in important processes such as neurogenesis and lineage specification, neurite outgrowth and growth cone dynamics, and synaptic plasticity where NMDAR-dependent signaling, and long term depression/potentiation are redox-regulated phenomena. HD animal models and iPSC studies have made it clear that the very same physiological processes are also affected in HD, and we will speculate on possible roles for NOX in the pathogenesis and development of disease. Finally, we also take into account the limited information on microglia in HD, and relate this to any contribution of NOX enzymes.